Childhood BMI is inversely associated with pubertal timing in normal-weight but not overweight boys. Issue 6 (13th October 2018) - Bygdell, Maria; Kindblom, Jenny M; Celind, Jimmy; Nethander, Maria; Ohlsson, Claes
ABSTRACT: Background: An inverse association between childhood body mass index (BMI; in kg/m 2 ) and pubertal timing is well established for girls. Among boys, studies are scarce and the results inconclusive. Objective: We aimed to determine the association between childhood BMI and age at peak height velocity (PHV) in boys. Design: We collected height and weight measurements between 6.5 and 22 y of age for boys born 1945–1961 (original cohort; n = 31, 971; mean ± SD childhood BMI: 15.74 ± 1.41; age at PHV: 14.06 ± 1.11 y) and 1981–1996 (replication cohort; n = 1465; childhood BMI: 16.47 ± 2.06; age at PHV: 13.71 ± 1.08 y) attending schools in Gothenburg, Sweden, and examined at mandatory military conscription. Age at PHV was obtained from curve-fitting of measured heights with the use of a modified Infancy-Childhood-Puberty model. Results: In the original cohort, childhood BMI was inversely associated with age at PHV ( P < 0.001) and a significant quadratic term for childhood BMI ( P < 0.001) indicated the nonlinearity of this association. Via piecewise linear regression, we identified a threshold for the association at a childhood BMI of 18.42. A significant inverse association was observed below (β: −0.17 y/BMI unit; 95% CI: −0.18, −0.16 y/BMI unit) but not above (β: 0.02 y/BMI unit; 95% CI: −0.03, 0.06 y/BMI unit) this childhood BMI threshold. For every unit increase in childhood BMI, age at PHV was ∼2 mo earlier up to the childhood BMI threshold. Similar results were observed in the replication cohort, demonstrating a significant inverse association below (β: −0.16; 95% CI: −0.21, −0.11) but not above (β: −0.03; 95% CI: −0.11, 0.05) the childhood BMI threshold. The identified threshold was close to the cutoffs for overweight at 8 y of age, and childhood BMI was inversely associated with age at PHV below but not above the overweight cutoffs. Conclusions: The present findings establish an inverse association between childhood BMI and pubertal timing in normal-weight but not overweight boys.